Glycolysis Inhibition Alleviates Cardiac Fibrosis After Myocardial Infarction by Suppressing Cardiac Fibroblast Activation - Chen, Zhi-Teng; Gao, Qing-Yuan; Wu, Mao-Xiong; Wang, Meng; Sun, Run-Lu; Jiang, Yuan; Guo, Qi; Guo, Da-Chuan; Liu, Chi-Yu; Chen, Si-Xu; Liu, Xiao; Wang, Jing-Feng; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective: To explore the role of glycolysis in cardiac fibroblast (CF) activation and cardiac fibrosis after myocardial infarction (MI). Method:In vivo: 2-Deoxy-D-glucose (2-DG), a glycolysis inhibitor, was injected into the abdominal cavity of the MI or sham mice every day. On the 28th day, cardiac function was measured by ultrasonic cardiography, and the hearts were harvested. Masson staining and immunofluorescence (IF) were used to evaluate the fibrosis area, and western blot was used to identify the glycolytic level. In vitro, we isolated the CF from the sham, MI and MI with 2-DG treatment mice, and we also activated normal CF with transforming growth factor-β1 (TGF-β1) and block glycolysis with 2-DG. We then detected the glycolytic proteins, fibrotic proteins, and the concentrations of lactate and glucose in the culture medium. At last, we further detected the fibrotic and glycolytic markers in human fibrotic and non-fibrotic heart tissues with masson staining, IF and western blot. Result: More collagen and glycolytic protein expressions were observed in the MI mice hearts. The mortality increased when mice were treated with 2-DG (100 mg/kg/d) after the MI surgery (Log-rank test, P < 0.05). When the dosage of 2-DG declined to 50 mg/kg/d, and the treatment was started on the 4th day after MI, no statistical difference of mortality between the two groups was observed (Log-rank test, P = 0.98). The collagen volume fraction was smaller and the fluorescence signal of α-smooth muscle actin (α-SMA) was weaker in mice treated with 2-DG than PBS. In vitro, 2-DG could significantly inhibit the increased expression of both the glycolytic and fibrotic proteins in the activated CF. Conclusion: Cardiac fibrosis is along with the enhancement of CF activation and glycolysis. Glycolysis inhibition can alleviate cardiac fibroblast activation and cardiac fibrosis after myocardial infarction.